An explanation of the apparent bridgman effect in merchant's orthogonal cutting results - Oxley, P. L. B.; Welsh, M. J. M. (College of Aeronautics)
Abstract In Merchant's modified shear angle solution it is assumed following Bridgman that the shear strength of the work material is a function of the hydrostatic stress. Although Merchant's experimental results confirm the assumed relation subsequent workers have failed to obtain such agreement. In this paper it is shown that Merchant's results can be explained independently of the Bridgman effect by considering the variable flow stress properties of the work material, which are strain-rate dependent.